Implementation of the Problem Based Learning Model in Improving Cognitive Learning Outcomes of Class V Students on Pancasila Educational Content at SD Negeri 1 Kunjeng - Jannah, Laila Rochatul; Huda , Choirul; Baedowi, Sunan (Indonesian Academy of Social and Religious Research (IASRR), 2024)
The aim of this research is to find out how the implementation of the problem-based learning model improves the cognitive learning outcomes of class V students on the content of Pancasila Education at SD Negeri 1 Kunjeng. This type of research is quantitative research using a One-Group Pretest-Posttest Design research design. The population of this research is class V of SD Negeri 1 Kunjeng with a sample of 38 students. Data collection methods through interviews, tests, questionnaires and documentation. Based on the results of the research that has been carried out, it can be seen that the t-test calculation found a significant value, namely 0.000 < 0.005, so Ho is rejected and Ha is accepted. After that, the N-Gain test was calculated and obtained an average of 0.77 with a percentage of 77.16%, so according to the N-gain index the results have an effective level of effectiveness. The conclusion is that the implementation of the problem-based learning model has an effect on improving the cognitive learning outcomes of class V students with Pancasila Education content at SD Negeri 1 Kunjeng